Insights into the voltage-gated sodium channel, NaV1.8, and its role in visceral pain perception - Heinle, J. Westley; Dalessio, Shannon; Janicki, Piotr; Ouyang, Ann; Vrana, Kent E.; Ruiz-Velasco, Victor; Coates, Matthew D. (Frontiers in Pharmacology, 2024)
Pain is a major issue in health care throughout the world. It remains one of the major clinical issues of our time because it is a common sequela of numerous conditions, has a tremendous impact on individual quality of life, and is one of the top drivers of cost in medicine, due to its influence on healthcare expenditures and lost productivity in those affected by it. Patients and healthcare providers remain desperate to find new, safer and more effective analgesics. Growing evidence indicates that the voltage-gated sodium channel Nav1.8 plays a critical role in transmission of pain-related signals throughout the body. For that reason, this channel appears to have strong potential to help develop novel, more selective, safer, and efficacious analgesics. However, many questions related to the physiology, function, and clinical utility of Nav1.8 remain to be answered. In this article, we discuss the latest studies evaluating the role of Nav1.8 in pain, with a particular focus on visceral pain, as well as the steps taken thus far to evaluate its potential as an analgesic target. We also review the limitations of currently available studies related to this topic, and describe the next scientific steps that have already been undertaken, or that will need to be pursued, to fully unlock the capabilities of this potential therapeutic target.